Effects of conventional and sugar-free energy drinks intake in runners: a double-blind, randomized, placebo-controlled crossover clinical trial - Reis, H. H.; Lima, L. M.; Reis, V. E.; Mota-Júnior, R. J.; Soares-Júnior, D. T.; Sillero-Quintana, M.; Rasmussen, H. E.; Carneiro-Júnior, M. E.; Marins, J. B. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study evaluated the effects of two types of energy drinks (ED) intake in trained runners. METHODS: A double-blind randomized placebo-controlled clinical trial was conducted over 6 weeks. Participants and beverages were allocated by randomization. Twelve men 23±2.6 years, 177±3.4 cm, 74.4±5.5 kg, VO2max=59.8±5.5 mL/k/min] ingested either a conventional energy drink containing carbohydrates and 3 mg/kg of caffeine, (ED1), a sugar-free energy drink 3 mg/kg of caffeine (ED2), or a carbohydrate-containing, decaffeinated placebo (PL) 40-minutes before an exercise protocol. Sprint time, rate of perceived exertion (RPE), respiratory exchange ratio (RER), blood pressure (BP), heart rate and plasmatic glucose were evaluated during the experimental protocol. RESULTS: Performance improved after consuming both ED (P<0.004 ED1 and P=0.001 ED2) with lower RPE (P<0.05 for ED1 and P<0.05 for ED2) compared to PL. Consumption of ED2 decreased RER values at 0-5 minutes and 40-45 minutes (P<0.001), and ED1 increased systolic BP (P<0.05) during exercise compared to PL. There were no differences in the evaluated parameters between EDs (P>0.05). CONCLUSIONS: Consumption of conventional or sugar free ED represents a valid ergogenic strategy to improve acute performance with reduction of RPE. However, intake of a conventional ED warrants caution, mainly because the effects on systolic BP.